2013
DOI: 10.1111/1574-6968.12220
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating efficacy of bacteriophage therapy againstStaphylococcus aureusinfections using a silkworm larval infection model

Abstract: Silkworm larva has recently been recognized as an alternative model animal for higher mammals to evaluate the effects of antibiotics. In this study, we examined the efficacy of the bacteriophage (phage) therapy, which harnesses phages as antibacterial agents, against Staphylococcus aureus infections, using the silkworm larval infection model. Two newly isolated staphylococcal phages, S25-3 and S13', were used as therapeutic phage candidates. They were assigned to two different lytic phage genera, Twort-like an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 23 publications
(29 reference statements)
1
36
0
Order By: Relevance
“…Using two new phages to infect the bacterium, we found no adverse effects on the silkworm, but the phages did destroy the bacteria cells 3 . Our results using silkworm larvae were similar to those using these phages against S. aureus infections in mice.…”
Section: The Silk Roadmentioning
confidence: 88%
“…Using two new phages to infect the bacterium, we found no adverse effects on the silkworm, but the phages did destroy the bacteria cells 3 . Our results using silkworm larvae were similar to those using these phages against S. aureus infections in mice.…”
Section: The Silk Roadmentioning
confidence: 88%
“…The transduction activities of other phages are also of interest in staphylococci. Thus, we examined the generalized transduction activity and host range using three types of staphylococcal phages: siphophages fMR25 and 80, podophage S13 0 and myophage S25-3 Hoshiba et al, 2010;Takemura-Uchiyama et al, 2013) (Supplementary Table S2). Phages 80 and fMR25 were S. aureusspecific phages that exhibited transduction activities in S. aureus (Supplementary Table S1 and Supplementary Figure S4).…”
Section: Generalized Transduction In Staphylococcus Sppmentioning
confidence: 99%
“…Electron microscopy, genome size estimation and nucleoside analysis were conducted to characterize the phage, according to published methods (Uchiyama et al, 2008(Uchiyama et al, , 2012Takemura-Uchiyama et al, 2013). Phage S6 was shown to belong to the family Myoviridae with a genome size of ca.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, human trials with phages against a number of infections have confirmed their safety and shown that phage therapy can provide good results for untreatable chronic infections (12,13). Specifically, recent results showed the efficacy of phages in animal models, such as S. aureus septicemia in mice (14) and in silkworms (15). The safety and efficacy of phage products for removal of this bacterium in a sinusitis sheep model have also been proven (16).…”
mentioning
confidence: 98%